2007
DOI: 10.1016/j.stem.2007.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role of Thrombopoietin in Maintaining Adult Quiescent Hematopoietic Stem Cells

Abstract: The role of cytokines in regulation of hematopoietic stem cells (HSCs) remains poorly understood. Herein we demonstrate that thrombopoietin (THPO) and its receptor, MPL, are critically involved in postnatal steady-state HSC maintenance, reflected in a 150-fold reduction of HSCs in adult Thpo(-/-) mice. Further, whereas THPO and MPL proved not required for fetal HSC expansion, HSC expansion posttransplantation was highly MPL and THPO dependent. The distinct role of THPO in postnatal HSC maintenance is accompani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

26
436
1
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 485 publications
(477 citation statements)
references
References 58 publications
26
436
1
6
Order By: Relevance
“…The ability of p21 Cip1 to regulate quiescence of mainly HSCs have been reported earlier [3,[28][29][30]. In contrast to p21 Cip1 , p27 Kip1 and p57 Kip2 were not affected by hypoxia, although higher levels of p57 Kip2 were seen in CD34 -LT-HSCs compared to CD34 + ST-HSCs, as previously described [31][32][33]. It is possible that the expression of p57 Kip2 in LT-HSCs is already high due to its BM localization and in part by cytokine-induced expression of p57 Kip2 [31][32][33].…”
Section: Discussionsupporting
confidence: 78%
“…The ability of p21 Cip1 to regulate quiescence of mainly HSCs have been reported earlier [3,[28][29][30]. In contrast to p21 Cip1 , p27 Kip1 and p57 Kip2 were not affected by hypoxia, although higher levels of p57 Kip2 were seen in CD34 -LT-HSCs compared to CD34 + ST-HSCs, as previously described [31][32][33]. It is possible that the expression of p57 Kip2 in LT-HSCs is already high due to its BM localization and in part by cytokine-induced expression of p57 Kip2 [31][32][33].…”
Section: Discussionsupporting
confidence: 78%
“…These niche cells express a high level of HSC maintenance factors termed "niche factors", including Angiopoietin 1 (Ang-1) (Arai et al, 2004), stem cell factor (SCF) (Heissig et al, 2002), CXCL12 (Sugiyama et al, 2006;Katayama et al, 2006;Kollet et al, 2006), thrombopoietin (Tpo) (Qian et al, 2007;Yoshihara et al, 2007), Wnt (Fleming et al, 2008), Jagged 1 (Jag1) (Calvi et al, 2003;Butler et al, 2010), TGF-β (Yamazaki et al, 2011), osteopontin (OPN) (Nilsson et al, 2005;Stier et al, 2005) CXCL4 (Bruns et al, 2014, N-cadherin (Haug et al, 2008;Hosokawa et al, 2010a;2010b), and E-selectin (Winkler et al, 2012). There are, however, still controversies in the field regarding the precise HSC niche, and a better understanding of the elements that regulate HSCs is required.…”
Section: The Hsc Niche In the Teleost Kidneymentioning
confidence: 99%
“…In addition, c-MPL is present on hematopoietic stem cells. [33][34][35][36][37][38] Several studies have demonstrated that thrombopoietin or thrombopoietin receptor agonists could stimulate stem cells proliferation in vitro before bone marrow transplant. 35,36 Small molecule agonists of c-MPL can stimulate stem cells to differentiate not only to megakaryocytes, but also towards erythroid and myeloid precursors.…”
Section: Discussionmentioning
confidence: 99%
“…35,36 Small molecule agonists of c-MPL can stimulate stem cells to differentiate not only to megakaryocytes, but also towards erythroid and myeloid precursors. 35,37 Thrombopoietin or thrombopoietin receptor agonists, and c-MPL are part of a complex network of cytokines and receptors, whose delicate balance is crucial in the tuning of the process of hematopoietic differentiation. 34,36,37,39,40 The increased hematopoiesis seen in treated patients could be related to the effects of thrombopoietin receptor agonists on the stem cell reservoir or on early progenitors of each lineage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation